2005
DOI: 10.1037/1082-989x.10.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analytic Methods of Pooling Correlation Matrices for Structural Equation Modeling Under Different Patterns of Missing Data.

Abstract: Three methods of synthesizing correlations for meta-analytic structural equation modeling (SEM) under different degrees and mechanisms of missingness were compared for the estimation of correlation and SEM parameters and goodness-of-fit indices by using Monte Carlo simulation techniques. A revised generalized least squares (GLS) method for synthesizing correlations, weighted-covariance GLS (W-COV GLS), was compared with univariate weighting with untransformed correlations (univariate r) and univariate weightin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
108
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(119 citation statements)
references
References 44 publications
5
108
0
6
Order By: Relevance
“…For example, in the current study, the meta-analytic correlation for the relationship between complexity and burnout is obtained from studies that are different from the studies that are utilized to obtain the metaanalytic correlation for the relationship between physical demands and burnout. Research has found parameter estimates and chisquare tests to be biased when data in a meta-analytic matrix are missing not at random (Furlow & Beretvas, 2005). Thus, if effect sizes are missing not at random, the results may be subject to bias (Naragon-Gainey, 2010).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, in the current study, the meta-analytic correlation for the relationship between complexity and burnout is obtained from studies that are different from the studies that are utilized to obtain the metaanalytic correlation for the relationship between physical demands and burnout. Research has found parameter estimates and chisquare tests to be biased when data in a meta-analytic matrix are missing not at random (Furlow & Beretvas, 2005). Thus, if effect sizes are missing not at random, the results may be subject to bias (Naragon-Gainey, 2010).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Third, several limitations in the use of meta-analytic correlation matrices with regard to path analyses have been noted and investigated by researchers (Field, 2005;Furlow & Beretvas, 2005;Hafdahl, 2007;Hafdahl & Williams, 2009). These limitations primarily focus on the accuracy of parameter estimates and goodness-of fit-indices.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides fitting regression models on the pooled correlation matrix, MASEM has been extended to fit path models, exploratory factor analysis, confirmatory factor analysis, and structural equation models (e.g., Becker, 2000;Becker & Schram, 1994;S. F. Cheung, 2000;Furlow & Beretvas, 2005;Hafdahl, 2001;Shadish, 1996;Viswesvaran & Ones, 1995).…”
Section: Fixed-effects Modelsmentioning
confidence: 99%